The Language Used In Composing Email To Show A Professional Netiquette of Secretarial Students - Fredericka Krisma Setyatami; Gabriella Novianty Soedjarwo (Jurnal Administrasi dan Kesekretarisan, 2023)
Email communication has become an everyday occurrence in the modern digital era since it is believed to be an easy and fast way to reach a larger audience, even in various regions of the world. The purpose of this study is to analyze how students at Sekolah Tinggi Ilmu Komunikasi dan Sekretari Tarakanita (STARKI) behave when emailing their lecturer. Their emails were examined in accordance with the principle of effective email composition. This study also aims to reinforce the notion that good netiquette is a necessary ability in the current digital environment to raise the professionalism of secretaries in the workplace. In this investigation, document analysis was used. The information was gathered from the lecturer's email. In this article, the research results from the students' emails are presented. The subject line, email body, and language usage were all examined. Still currently, a lot of business emails are sent without adhering to the proper format and professionalism. The netiquette needs to be included in STARKI's curriculum since it is a secretarial school. It is crucial to include this content in the Business Writing course so that students may demonstrate professionalism by sending emails within business hours, using acceptable and official language, and organizing their information in the proper way.